INFLUENCER REVIEW TERHADAP MINAT BELI DI PLATFORM TIKTOK: MODERASI BRAND IMAGE PRODUK MS GLOW - Usnan Usnan; Muhammad Makruflis; Erfina Erfina (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
The most basic technology used by user is the use of the internet with all the activities and activities undertaken. Internet usage has been increasing every year since January 2013, the number of Indonesian internet users reached 213 million people, up 5.44%. there is openness of information and public acceptance that is enthusiastic about technological developments in order to advance change towards an information based society will be a benchmark as the high use of the internet. The researchers aimed to find out how influencer reviews influenced purchasing interest by moderating brand image on Ms Glow products. The research used quantitative data whose scale of survey scale was 1 to 5. The sample of 80 respondents who were millennial consumers using stickers. Data analysis techniques using moderated regression analysis SPSS v.29. the results of the study indicated that influencer reviews influenced purchasing interest positively with a result og sig. 0.001<0.05. where as the brand image moderation variable could not moderate the influencer review towards the purchase interest of Ms Glow product with sig. 0.863>0.05. then, the determination coefficient with a value of 39.9% with the remaining 60.1% was affected by external variables that were not present in this study. For adjusted r square there is a different between model 1 and model 2 of 0.383 and 0.375. this means that the brand image moderation variable is unable to moderate between the influencer review variable and the buying interest. Keywords: Influencer Review, Interest of Buying, Tiktok and Brand Image.